ADAPTATION AND VALIDATION OF DUNDEE POLYPROFESSIONALISM INVENTORY-1 FOR USE IN PAKISTAN - Shukr, Irfan (Journal of Ayub Medical College Abbottabad, 2014)
Department of Surgery, Army Medical College/Armed Forces Postgraduate Medical Institute, Rawalpindi, Pakistan Background: Medical colleges want academic integrity in medical students. This will require measurement of professionalism. Dundee Poly-professionalism Inventory-1 is one of the few validated tools available to measure academic integrity. The purpose was to validate the Dundee Poly-professionalism Inventory-1 for use in Pakistan. Methods: In this cross sectional study words and statements in the inventory that a majority of Pakistani students could not understand were replaced by simpler words, or sentences for better understanding of our students. Faculty reviewed the proposed sanctions for their appropriateness in the Pakistani setting. A stratified sample of 64 students, and 16 faculty members were invited to participate in the study. Results: Out of 64 students, 57 students responded (Response rate 89%). Out of 16 faculty members, 12 responded (response rate 75%).The language of 8 statements in the inventory that a majority of students could not understand was changed. 50% or more of faculty members considered that the statements in the inventory were appropriate. 9 faculty members (75%) suggested, '˜Making false entries in logbooks/signing such log books', and 10 faculty members (83%) suggested, '˜Writing/getting signed false certificates' should be included in the inventory. These were included in the validated questionnaire. Similarly 50% or more of faculty considered that the different types of sanctions and that the levels of sanctions were appropriate. Conclusion: In this customised form the Dundee Poly Professionalism Inventory-I can be used in Pakistan, and other South Asian countries to assess professionalism related to academic integrity. Keywords: Academic integrity, Poly Professional Inventory, Dundee, Pakistan